Exploring Cultural Knowledge through Sketches of Historical Sites in Makassar City: An Innovative Approach to Fine Arts Learning - Rasul; Andi Taslim Saputra (Tamaddun Life, 2026)
This study examined how historical-site-based sketching can strengthen fine arts learning and cultural knowledge among students in the Fine Arts Education Study Program at Makassar State University. The study responded to the limited use of Makassar’s historical sites as educational resources despite their architectural, historical, and cultural significance. It aimed to investigate the implementation and learning contribution of field-based sketching at the Makassar City Museum, Fort Rotterdam, Societeit de Harmonie, and Paotere Harbor. A qualitative case study design was employed. Data were collected through field observations, interviews, documentation, questionnaires, and analysis of students’ sketches. The data were analyzed thematically and interpreted through triangulation across sources and techniques. The findings show that direct sketching encouraged students to observe architectural proportions, perspective, line quality, textures, spatial relationships, and changing environmental conditions more attentively. Their sketches demonstrated stronger visual representation and contextual detail, while interviews and questionnaires indicated increased understanding of historical meanings, social functions, local identity, and heritage preservation. Students also reported greater engagement and confidence in discussing visual interpretations than in conventional studio-based learning. The study concludes that historical-site-based sketching can function as a contextual pedagogical model that integrates technical skill development with cultural literacy and heritage appreciation. The approach is particularly valuable when supported by preparatory historical orientation, guided field observation, reflective critique, and assessment that addresses both artistic and cultural dimensions. Further research should examine longer-term learning outcomes across broader participant groups and heritage settings.